Association Between Steno-Occlusive Middle Cerebral Artery and Basal Ganglia Perivascular Spaces - Du, Houwei; Chen, Chao; Ye, Chengbin; Lin, Feifei; Wei, Jin; Xia, Pincang; Chen, Ronghua; Wu, Sangru; Yuan, Qilin; Chen, Hongbin; Xiao, Yingchun; Liu, Nan (Frontiers in Neurology, 2020)
Objectives: Enlarged perivascular spaces in the basal ganglia (BG-EPVS) share common vascular risk factors with atherosclerosis. However, little is known about the relationship between steno-occlusive middle cerebral artery (MCA) and BG-EPVS. In this cross-sectional study, we aimed to test the hypothesis that severe MCA stenosis or occlusion is associated with increased MRI-visible BG-EPVS. Methods: We retrospectively reviewed 112 patients with a steno-occlusive MCA from Fujian Medical University Union Hospital between January 2014 and December 2018. We rated BG-EPVS, white matter hyperintensities (WMH), and lacunes as markers of cerebral small vessel disease (CSVD) on magnetic resonance image (MRI). The severity of steno-occlusive MCA was assessed by computed tomography angiography (CTA) and was classified into moderate (50-69%), severe (70-99%) and occlusion (100%). We evaluated the association of steno-occlusive MCA for >10 BG-EPVS using logistic regression model adjusted for age, gender, hypertension, MR-visible WMH and lacunes. We also compared the number of BG-EPVS between the affected side and unaffected side in patients with only unilateral steno-occlusive MCA. Results: In multivariable logistic regression analysis, age (OR 1.07, 95%CI 1.03–1.13, p = 0.003), hypertension (OR 2.77, 95% CI 1.02-7.51, p = 0.046), severe MCA stenosis (OR 3.65, 95% CI 1.12-11.87, p = 0.032) or occlusion (OR 3.67, 95% CI 1.20-11.27, p = 0.023) were significantly associated with >10 BG-EPVS. The number of BG-EPVS in the affected side was higher than the unaffected side in patients with severe MCA stenosis (12[9-14] vs 8[6-11], p = 0.001) or occlusion (11 [7–14]) vs 8 [5–11], p = 0.028). Conclusions: BG-EPVS were more prevalent in patients with severe MCA atherosclerosis. Our findings suggest a biological link between severe steno-occlusive MCA and increased BG-EPVS. These results need confirmation in prospective studies.